Familias Wayúu y el Síndrome de Down: Transformación, Experiencias y Lecciones de Vida. (2021)
At present, Down syndrome (DS) is considered one of the alterations most common and high incidence chromosomes in the world, which affects the capacities cognitive skills of people. And in families it usually causes transformations, this problem is little addressed in the department of La Guajira, therefore it is important to carry out investigations that take into account the family in the region with affected children. Therefore, Analyze the transformations, lessons and life experiences that families go through Wayúu with children with Down syndrome, becomes a pioneering project for approach the subject from the qualitative method of the Interpretative - narrative, grounded type.